CBT4BN: a randomized controlled trial of online chat and face-to-face group therapy for bulimia nervosa - Zerwas, Stephanie C.; Zimmer, Benjamin; Moessner, Markus; Kordy, Hans (Psychotherapy and psychosomatics, 2017)
Objective: Although cognitive-behavioral therapy (CBT) represents the first-line evidence-based psychotherapy for bulimia nervosa (BN), most individuals seeking treatment do not have access to this specialized intervention. We compared an Internet-based manualized version of CBT group therapy for BN conducted via a therapeutic chat group (CBT4BN) to the same treatment conducted via a traditional face-to-face group therapy (CBTF2F). Method: In a two-site, randomized, controlled noninferiority trial, we tested the hypothesis that CBT4BN would not be inferior to CBTF2F. A total of 179 adult patients with BN (2.6% males) received up to 16 sessions of group CBT over 20 weeks in either CBT4BN or CBTF2F, and outcomes were compared at the end of treatment and at the 12-month follow-up. Results: At the end of treatment, CBT4BN was inferior to CBTF2F in producing abstinence from binge eating and purging. However, by the 12-month follow-up, CBT4BN was mostly not inferior to CBTF2F. Participants in the CBT4BN condition, but not CBTF2F, continued to reduce their binge-eating and purging frequency from the end of treatment to the 12-month follow-up. Conclusions: CBT delivered online in a group chat format appears to be an efficacious treatment for BN, although the trajectory of recovery may be slower than face-to-face group therapy. Online chat groups may increase accessibility of treatment and represent a cost-effective approach to service delivery. However, barriers in service delivery such as state-specific license and ethical guidelines for online therapists need to be addressed.